2015
DOI: 10.1523/jneurosci.4376-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

GluA2 Trafficking Is Involved in Apoptosis of Retinal Ganglion Cells Induced by Activation of EphB/EphrinB Reverse Signaling in a Rat Chronic Ocular Hypertension Model

Abstract: EphB1, expressed in Müller cells, and ephrinB2, expressed in both Müller cells and retinal ganglion cells (RGCs), constitute an EphB/ ephrinB reverse signaling in RGCs. Whether and how this reverse signaling is involved in RGC apoptosis in a rat chronic ocular hypertension (COH) model was investigated. In the COH model, both EphB1 and ephrinB2 were significantly increased and the reverse signaling was activated, which was accompanied by increased protein levels of phosphorylated ( -permeable GluA2-lacking AMPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 73 publications
6
66
0
Order By: Relevance
“…Similarly seen in our current in vitro study, different models of ocular hypertension have shown increased expression of AMPARs in RGC somas 21,116 and ectopically at the optic nerve head. 117 The application of an AMPAR antagonist or blocker was able to prevent the loss of RGCs in these models; however, it is not known if these neurons and other retina cells containing AMPARs are impaired; thus, possibly effecting vision acuity and function.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly seen in our current in vitro study, different models of ocular hypertension have shown increased expression of AMPARs in RGC somas 21,116 and ectopically at the optic nerve head. 117 The application of an AMPAR antagonist or blocker was able to prevent the loss of RGCs in these models; however, it is not known if these neurons and other retina cells containing AMPARs are impaired; thus, possibly effecting vision acuity and function.…”
Section: Discussionsupporting
confidence: 88%
“…The apoptosis of RGCs is the main cause of optic nerve damage in glaucoma, and numerous factors are involved in this process [52,53] . In addition, miRNAs exist in the retina [54] , and miRNAs are expressed in the retina of eyes with advanced glaucomatous damage [55] .…”
Section: The Relationship Between Mirna and The Apoptosis Of Rgcs Caumentioning
confidence: 99%
“…[24][25][26] For immunofluorescence double labeling, the sections were incubated with a cocktail of two primary antibodies overnight at 48C. The primary antibodies used in the present study included polyclonal goat or rabbit anti-GHSR-1a (1:50; Santa Cruz Biotechnology, Santa Cruz, CA, USA, or Sigma-Aldrich Corp., St. Louis, MO, USA), polyclonal goat anti-ghrelin (1:50), monoclonal mouse anti-Brn-3a (1:100; Santa Cruz Biotechnology), and monoclonal mouse anti-glial fibrillary acidic protein (anti-GFAP, 1:500; Sigma).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…23,25,27 Protein samples (20 lg) were separated by using 10% or 15% SDS-PAGE. The primary antibodies included monoclonal mouse anti-b-actin (1:8000) and monoclonal mouse anti-GFAP (1:1000; Sigma), polyclonal goat anti-GHSR1a (1:1000), polyclonal goat anti-ghrelin (1:1000), polyclonal rabbit anti-phospho-Akt (1:1000), polyclonal goat anti-Akt (1:1000), polyclonal rabbit anti-mTOR (1:1000), goat anticaspase3 (1:1000; Santa Cruz Biotechnology), rabbit anti-LC3 (1:1000), rabbit anti-beclin1 (1:1000; Abcam, Cambridge, MA, USA), and rabbit anti-phospho-mTOR (1:1000; Cell Signaling Technology, Danvers, MA, USA).…”
Section: Western Blot Analysesmentioning
confidence: 99%
See 1 more Smart Citation